1985
DOI: 10.1007/bf00633483
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte populations in multiple sclerosis

Abstract: In 36 patients representing different clinical stages of multiple sclerosis (MS) (9 patients with acute exacerbations; 21 patients in remission; 5 patients with chronic progressive MS) determinations of T lymphocyte populations using monoclonal antibodies against surface antigens (OKT3 (pan T cells), OKT4 (helper T cells), OKT8 (cytotoxic/suppressor T cells] were performed. Compared to the control group (40 healthy individuals) a clear elevation of the T4/T8 ratio was found in acute exacerbations and to a less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Since the disease manifests itself in CNS plaques, significant pathology in other organs is limited; however, immune abnormalities are detectable in the peripheral blood. The presence of myelin basic protein (MBP)-specific T cells has been demonstrated in the peripheral blood (9,31), and MS patients have been found to have elevated ratios of CD4 ϩ /CD8 ϩ cells (5,14,30,38) and decreased percentages of CD28 Ϫ CD8 ϩ suppressor cell precursors in the peripheral blood (5). Recent studies have indicated that cytokines play an important role in the initiation, progres-sion, remission, and exacerbation of MS. Gamma interferon (IFN-␥) and tumor necrosis factor alpha have been found in the CNS plaque material of patients with MS and animals with experimental allergic encephalomyelitis (EAE), the best animal model of MS (25,35).…”
mentioning
confidence: 99%
“…Since the disease manifests itself in CNS plaques, significant pathology in other organs is limited; however, immune abnormalities are detectable in the peripheral blood. The presence of myelin basic protein (MBP)-specific T cells has been demonstrated in the peripheral blood (9,31), and MS patients have been found to have elevated ratios of CD4 ϩ /CD8 ϩ cells (5,14,30,38) and decreased percentages of CD28 Ϫ CD8 ϩ suppressor cell precursors in the peripheral blood (5). Recent studies have indicated that cytokines play an important role in the initiation, progres-sion, remission, and exacerbation of MS. Gamma interferon (IFN-␥) and tumor necrosis factor alpha have been found in the CNS plaque material of patients with MS and animals with experimental allergic encephalomyelitis (EAE), the best animal model of MS (25,35).…”
mentioning
confidence: 99%
“…Since the disease manifests itself in central nervous system plaques, significant pathology in other organs is limited; however, immune abnormalities are detectable in the peripheral blood. The presence of myelin basic protein-specific T cells has been demonstrated in the peripheral blood (6,24), and MS patients have been found to have elevated ratios of CD4 ϩ and CD8 ϩ cells (9,21,28). Taking into account the well-documented immunoregulatory abnormalities in MS, we have performed a comprehensive peripheral blood immunophenotype survey of MS patients and normal controls.…”
mentioning
confidence: 99%
“…1). It has been well documented that MS patients have an elevated CD4/CD8 ratio in both their peripheral blood (9,21,28) and their cerebrospinal fluid (11,14). Our analysis of T-cell subsets further confirmed those earlier observations that MS patients indeed have a significant elevation in the peripheral blood CD4 ϩ /CD8 ϩ T-cell ratio.…”
mentioning
confidence: 99%